2019
DOI: 10.1002/slct.201902997
|View full text |Cite
|
Sign up to set email alerts
|

Etidronic Acid Promoted Sequential One‐Pot Strategy for the Synthesis of 1H‐Imidazo[1,2‐b]pyrazoles: A Green Catalyst for Groebke‐Blackburn‐Bienaymé Reaction

Abstract: A development of Groebke‐Blackburn‐Bienaymé (GBB) reaction was shown by the application of Etidronic acid as a green catalyst. A number of 1H‐imidazo[1,2‐b]pyrazoles derivatives were prepared via multicomponent GBB reaction in one pot sequential steps by the condensation of 5‐amino‐1H‐pyrazole, aldehyde and isonitrile. Here, we have demonstrated the development of GBB protocol by the utility of Etidronic acid in milder reaction medium to modify and simplify the existing synthetic strategies that removes hazard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…An efficient approach to the green synthesis of glycoluryls in an aqueous medium using P 4 O 10 as a catalyst, under mild conditions with the possibility of recycling both solvent and catalyst, is reported in Ref. [39] More recently, in a number of works [40][41][42] it was found that etidronic acid (HEDP) proved to be a convenient "green" catalyst in 3-component reactions of the formation of dihydropyrimidones using carbonyl compounds with an active methylene group, urea and aldehydes as under traditional conditions, [40,41] and under microwave synthesis. [42] However, examples of the use of HEDP as a catalyst in the reactions of 1, 2-dicarbonyl compounds with ureas are still not known.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An efficient approach to the green synthesis of glycoluryls in an aqueous medium using P 4 O 10 as a catalyst, under mild conditions with the possibility of recycling both solvent and catalyst, is reported in Ref. [39] More recently, in a number of works [40][41][42] it was found that etidronic acid (HEDP) proved to be a convenient "green" catalyst in 3-component reactions of the formation of dihydropyrimidones using carbonyl compounds with an active methylene group, urea and aldehydes as under traditional conditions, [40,41] and under microwave synthesis. [42] However, examples of the use of HEDP as a catalyst in the reactions of 1, 2-dicarbonyl compounds with ureas are still not known.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, in a number of works [ 40–42 ] it was found that etidronic acid (HEDP) proved to be a convenient “green” catalyst in 3‐component reactions of the formation of dihydropyrimidones using carbonyl compounds with an active methylene group, urea and aldehydes as under traditional conditions, [ 40,41 ] and under microwave synthesis. [ 42 ] However, examples of the use of HEDP as a catalyst in the reactions of 1, 2‐dicarbonyl compounds with ureas are still not known.…”
Section: Introductionmentioning
confidence: 99%